1998
DOI: 10.1021/jp981482s
|View full text |Cite
|
Sign up to set email alerts
|

Supported Vanadium Oxide Catalysts: Quantitative Spectroscopy, Preferential Adsorption of V4+/5+, and Al2O3 Coating of Zeolite Y

Abstract: A series of supported vanadium oxide catalysts were prepared by the incipient wetness method as a function of the support composition (Al 2 O 3 , SiO 2 , and USY), the metal oxide loading (0-1 wt %), and the impregnation salt (vanadyl sulfate and ammonium vanadate). These catalysts have been studied by combined DRS-ESR spectroscopies in order to quantify the amount of V 4+ and V 5+ and to unravel their coordination geometries. These spectroscopic fingerprints have been used to study the preferential adsorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
65
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 101 publications
(71 citation statements)
references
References 28 publications
6
65
0
Order By: Relevance
“…This implies insight in the adsorption properties of supported vanadium oxides. In a recent study, the preferential adsorption of V 4+/5+ ions on SiO 2 , Al 2 O 3 and USY has been studied with combined DRS-ESR spectroscopies in quite detail [210]. By taking the spectroscopic fingerprints of V 4+/5+ on these supports as reference spectra it was possible to monitor the preferential adsorption of V 4+/5+ onto physical mixtures of these oxides.…”
Section: Catalyst Deactivationmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies insight in the adsorption properties of supported vanadium oxides. In a recent study, the preferential adsorption of V 4+/5+ ions on SiO 2 , Al 2 O 3 and USY has been studied with combined DRS-ESR spectroscopies in quite detail [210]. By taking the spectroscopic fingerprints of V 4+/5+ on these supports as reference spectra it was possible to monitor the preferential adsorption of V 4+/5+ onto physical mixtures of these oxides.…”
Section: Catalyst Deactivationmentioning
confidence: 99%
“…It was shown that both V 4+ and V 5+ ions were preferentially adsorbed on Al 2 O 3 and showed a much smaller preference for USY and SiO 2 . Based on this observation, a novel method was developed to coat the external surface of USY with a thin film of Al 2 O 3 [210,211]. This method is based on the deposition of USY with the so-called Keggin ion, [Al 13 O 4 (OH) 24 (H 2 O) 12 ] 7+ , which is too big to enter the USY channels or pores.…”
Section: Catalyst Deactivationmentioning
confidence: 99%
“…Vanadium Passivation. In a previous paper 6 we have studied the preferential adsorption and mobility of vanadium species on different oxidic supports. We found that both V 4+ and V 5+ ions show the following preference order: Al 2 O 3 > SiO 2 g USY.…”
Section: Preparation Of the Keggin Ion Solutions And [Almentioning
confidence: 99%
“…The efficiency of the proposed method, based on the deposition of USY with the so-called Keggin ion, [Al 13 O 4 (OH) 24 (H 2 O) 12 ] 7+ , was only indirectly proven via electron spin resonance of the vanadium impregnated materials. 6 A more detailed characterization of the Al species deposited on the external surface of the zeolite is obviously necessary.…”
Section: Introductionmentioning
confidence: 99%
“…By introducing catalytically active metal-connecting points or functional groups into the highly porous MOF structure, MOFs exhibit clear advantages in heterogeneous catalysis. Moreover, unlike traditional immobilized catalysts 9,10,11 , the active catalytic sites in MOFs are well protected by the coordination bonds which prevents leaching to a higher extent. Although the research in this field is relatively new, MOFs have been studied as catalysts in hydrogenation and oxidation reactions 12,13,14,15,16,17,18 enantioselective reactions 19,20,21 , photocatalysis 22 , carbonyl cyanosilylation 23,24,25 , hydrodesulfurization 26 and esterification 27 .…”
Section: Introductionmentioning
confidence: 99%